TRANSFORMASI LAYANAN ADMINISTRASI DIGITAL: SEBUAH KAJIAN INOVASI TEKNOLOGI PENCATATAN SIPIL “KNG” KLAMPID NEW GENERATION DI KOTA SURABAYA - Dalilah, Camilla; Fanida, Eva Hany (Publika, 2024)
The Surabaya City Department of Population and Civil Registration presents a digital innovation inpopulation and civil registration administration services through an application named "KNG" or "KlampidNew Generation". However, in its implementation, several issues were identified, such as unclear installationprocesses that frequently change and limited accessibility for residents outside Surabaya. This study aims todescribe the use of the application in providing population and civil registration services through the KNGapplication. The research method used is descriptive with a qualitative approach. The focus of this study isbased on the digital innovation strategy framework by Nylén and Holmström (2015). The research wasconducted at the Surabaya City Department of Population and Civil Registration using interview,observation, and documentation techniques. This study employs narrative analysis techniques, including datacollection, data reduction, data presentation, and drawing conclusions. The results show that users aresatisfied with the simple and easy-to-understand interface of the KNG application. KNG application offersvalue propositions with bundled services and clear task distribution. Continuous improvement inunderstanding and teamwork in evaluating the KNG application, along with improvisation and coordinationamong staff, ensures the optimal use of KNG application. Based on the research findings, the followingsuggestions are made: 1) There should be clarity regarding other versions of KNG, including mobileapplication versions that can be installed on Android and iOS systems. 2) Residents outside Surabaya shouldbe granted access to certain features available in the KNG application.